PENYELESAIAN MASALAH PENERBITAN SERTIPIKAT BERDASARKAN PEMALSUAN SURAT OLEH KANTOR PERTANAHAN - Setyadji, Sri; Manurung, Ahmath Indra Fernando (LPPM, Universitas Muhammadiyah Riau, 2025)
Obtaining legal certainty over land is a right of every citizen, and numerous cases of document forgery have plagued the ranks of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN). To resolve land disputes, strategic policies are needed with the aim of providing legal certainty and justice regarding the control, ownership, use, and utilization of land. Resolution is carried out based on the ministry's initiative or complaints from the public to the relevant ministry. Coordination between the ministry and the Regency/Municipal Land Office is essential to collect data, conduct analysis, and provide recommendations for case resolution. Land certificates may be annulled due to administrative reasons and miscalculations of land area. The annulment of certificates can be executed through a court decision or by the Ministry of ATR/BPN. In certificate annulment, the contrarius actus principle is applied, meaning that the administrative body or official that issued the decision also has the authority to revoke it. The annulment of legal products is conducted if there is an administrative and/or legal defect as stipulated in Article 35 of the Ministerial Regulation of ATR/Head of BPN No. 21/2020. In administrative law, the Ministry of ATR/BPN plays a crucial role in determining the authority of officials and ensuring legal certainty.